Analytical Model for Critical Impact Energy of Spalling and Penetration in Concrete Wall - Qadir Bux alias Imran Latif; Ismail Abdul Rahman; Ahmad Mujahid Ahmad Zaidi; Kamran Latif; Aftab Hameed; Sasitharan Nagapan (Institute of Advanced Engineering and Science, 2012)
Penetration is the basic element of designing protective concrete structure against the local impact of hard projectile. Conventional, un-conventional, and sensitive structures should have to be designed as self-protective structures in order to resist natural disaster, consciously engendered unpleasant incidents, or/and against accidently occur incidents in nuclear plants, local industries etc.. When hard projectile collides with concrete wall, it is the critical impact energy of the projectile that deforms concrete wall. Critical impact energy is the dominant cause of penetration in concrete structures. Therefore, it is vital to study critical impact energy that causes penetration. An analytical model is developed to predict the required critical impact energy for spalling and tunneling and maximum penetration without rear effects in concrete walls when it is impacted with hard projectile. The newly developed analytical model is examined for CRH =2.0, 3.0. It was found that the predicted results from analytical model are in close relation with experimental data with less than (8%) and (17%) error in case of CRH =2.0 and 3.0. Furthermore, Chen and Li nose shape factor is modified as (Ni), with introduction of empirical frictional factor (Nf). It was found that the predicted results from analytical model with proposed nose shape (Ni) are in close relation with experimental data in all cases as compared to predicted results with traditional Li and Chen nose shape (N*). In general, the analytical model generates encouraging prediction which is consistent and follows a general trend of experimental results. Therefore, it is suggested that the proposed analytical model is conservative.